RNA interference can be used to disrupt gene function in tardigrades - Tenlen, Jennifer R.; McCaskill, Shaina; Goldstein, Bob (Development Genes and Evolution, 2013)
How morphological diversity arises is a key question in evolutionary developmental biology. As a long-term approach to address this question, we are developing the water bear Hypsibius dujardini (Phylum Tardigrada) as a model system. We expect that using a close relative of two well-studied models, Drosophila (Phylum Arthropoda) and Caenorhabditis elegans (Phylum Nematoda), will facilitate identifying genetic pathways relevant to understanding the evolution of development. Tardigrades are also valuable research subjects for investigating how organisms and biological materials can survive extreme conditions. Methods to disrupt gene activity are essential to each of these efforts, but no such method yet exists for the Phylum Tardigrada. We developed a protocol to disrupt tardigrade gene functions by double-stranded RNA-mediated RNA interference (RNAi). We showed that targeting tardigrade homologs of essential developmental genes by RNAi produced embryonic lethality, whereas targeting green fluorescent protein did not. Disruption of gene functions appears to be relatively specific by two criteria: targeting distinct genes resulted in distinct phenotypes that were consistent with predicted gene functions and by RT-PCR, RNAi reduced the level of a target mRNA and not a control mRNA. These studies represent the first evidence that gene functions can be disrupted by RNAi in the phylum Tardigrada. Our results form a platform for dissecting tardigrade gene functions for understanding the evolution of developmental mechanisms and survival in extreme environments.